New potential for enhancing concomitant chemoradiotherapy with FDA approved concentrations of cisplatin via the photoelectric effect. Issue 1 (February 2015) - Altundal, Yucel; Cifter, Gizem; Detappe, Alexandre; Sajo, Erno; Tsiamas, Panagiotis; Zygmanski, Piotr; Berbeco, Ross; Cormack, Robert A.; Makrigiorgos, Mike; Ngwa, Wilfred
Abstract We predict, for the first time, that by using United States Food and Drug Administration approved concentrations of cisplatin, major radiosensitization may be achieved via photoelectric mechanism during concomitant chemoradiotherapy (CCRT). Our analytical calculations estimate that radiotherapy (RT) dose to cancer cells may be enhanced via this mechanism by over 100% during CCRT. The results proffer new potential for significantly enhancing CCRT via an emerging clinical scenario, where the cisplatin is released in-situ from RT biomaterials loaded with cisplatin nanoparticles.